Prevalence, Management, and Outcome of Syphillis in Low Income Countries: A Comprehensive Systematic Review - Yulianto, Ronald; Gunawan, Ellen Aristika (International Medical Journal Corp. Ltd, 2024)
Background: According to the World Health Organization’s (WHO) 2017 estimate, there were 18 million prevalent cases of syphilis worldwide. Syphilis was a significant public health problem before the antibiotic era and remained so to date, particularly with the increase in the magnitude of acquired immunodeficiency virus. Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: The epidemiology of syphilis indicates that the magnitude of syphilis has increased in selected high-income population groups, while the disease has remained endemic in low and middle-income countries.